2023
DOI: 10.3390/membranes13050489
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Nanoplatforms Based on Graphene Oxide and Neurotrophin-Mimicking Peptides

Abstract: Neurotrophins (NTs), which are crucial for the functioning of the nervous system, are also known to regulate vascularization. Graphene-based materials may drive neural growth and differentiation, and, thus, have great potential in regenerative medicine. In this work, we scrutinized the nano–biointerface between the cell membrane and hybrids made of neurotrophin-mimicking peptides and graphene oxide (GO) assemblies (pep−GO), to exploit their potential in theranostics (i.e., therapy and imaging/diagnostics) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…The secreted BDNF repairs nerve tissues by inducing EC survival and angiogenic tube formation, and NTs induce axonal growth by promoting the expression of angiogenic factors, such as VEGF. 72 Angiogenesis is induced by paracrine factors in SCs and ECs, which enhance neuronal regeneration. Additionally, the poor survival of transplanted SCs and ECs limits their therapeutic effect.…”
Section: Mcc-se Transplantation Promoted Angiogenesis Following Scimentioning
confidence: 99%
“…The secreted BDNF repairs nerve tissues by inducing EC survival and angiogenic tube formation, and NTs induce axonal growth by promoting the expression of angiogenic factors, such as VEGF. 72 Angiogenesis is induced by paracrine factors in SCs and ECs, which enhance neuronal regeneration. Additionally, the poor survival of transplanted SCs and ECs limits their therapeutic effect.…”
Section: Mcc-se Transplantation Promoted Angiogenesis Following Scimentioning
confidence: 99%
“…MD investigations have also demonstrated the graphene's capability to elicit toxicity by interfering with protein-protein interactions (PPI). Simulations of PPI in the presence and absence of graphene showed that graphene inserted into PP led to the destabilization of hydrophobic interactions, disrupting the protein complex [99]; see Figure 3 Molecular dynamics simulations were carried out to study the interface between neurotrophin-mimicking peptides [100][101][102] non-covalently linked to the surface of GO [103]. Among the peptides under investigation, NGF (1-14) exhibited the strongest interaction with the GO substrate.…”
Section: Basic Mechanisms and Peculiar Properties Of The Nano-biointe...mentioning
confidence: 99%
“…Notably, the glutamic acid residue assumes a crucial role since this moiety appears highly distanced from the surface in the case of BDNF (1-12), which coincides with the peptide displaying the lowest interaction energy; see Figure 4. Molecular dynamics simulations were carried out to study the interface between neurotrophin-mimicking peptides [100][101][102] non-covalently linked to the surface of GO [103]. Among the peptides under investigation, NGF (1-14) exhibited the strongest interaction with the GO substrate.…”
Section: Basic Mechanisms and Peculiar Properties Of The Nano-biointe...mentioning
confidence: 99%